Rating of perceived exertion is a stable and appropriate measure of workload in judo - Bromley, S. J.; Drew, M. K.; McIntosh, A.; Talpey, S. (Journal of Science and Medicine in Sport, 2018)
Objectives: Heart rate (HR), blood lactate concentration [La] and/or rating of perceived exertion (RPE) have been utilised to monitor judo training load in technical and randori (competition training) sessions, but are yet to be investigated in mixed sessions containing both elements. Therefore the purpose of this study was to: (1) determine the stability of these variables, and (2) to assess the efficacy of RPE as a load variable for mixed judo sessions. Design: Cross-sectional study. Methods: Twenty-nine athletes attended two mixed training sessions at an international training camp. Bout and session characteristics, including RPE, physical and mental effort, heart rate (HR) and post-session [La] were recorded. A two-way random-effects intra-class correlation assessed variable stability. Multilevel mixed-effects ordered logistic regression investigated relationships between RPE and other variables for bouts and sessions. Results: Average and minimum HR across sessions correlated highly (ICC = 0.95 and 0.94, respectively). Good correlations existed between [La], session-RPE and mental effort, and fair correlation of max HR and physical effort. No relationships existed between [La]/HR and session-RPE. A unit increase in bout-RPE resulted in a 2.09 unit increase in physical, or a 1.36 unit increase in mental, effort holding all other bout variables constant. Gender and competitive level did not influence statistical models. Conclusions: Results provide further evidence that RPE can be used across a range of competitive levels and genders to monitor workload of mixed sessions and individual randori in judo. Physical effort may play a larger role than mental effort when athletes reflect on exertion during training. ABSTRACT FROM AUTHOR